Singapore girl, you're a great way to fly : examining flight attendants' perceptions on gender stereotypes - So, Yinn Yann (2014)
This paper explores how flight attendants perceive gender stereotypes and gender ideologies embedded in their occupation, with references to Singapore International Airlines (SIA) and her corporate icon, the Singapore Girl (SG). As an icon, the SG is also an embodiment of multiple meanings subjected to varying interpretations by different parties. Not only is the representation of SG salient throughout SIA’s advertisements, it also plays an important role in shaping the gendered performances of the flight attendants at work and beyond. This paper attempts to approach the research question through several methods. Firstly, the paper will analyze and deconstruct the meanings embedded in the representation of SG. Secondly, participant observation offers insight on the socialization of the flight attendants into their roles in SIA. Lastly, semi-structured interviews with flight attendants are conducted to find out how they negotiate with the gender stereotypes and how they are affected by it. The results show that both stewards and stewardesses agree that SG is a worthy icon, but develop different interpretations of the SG and the role she plays in SIA.